Transjugular Intrahepatic Portosystemic Shunt. (31st August 2022) - Tyagi, Ravi; Gonzalez, Ana; Surabhi, Divya Meher; Navuluri, Rakesh
Abstract : Chronic liver disease is the 11th leading cause of mortality in the United States.1 Portal hypertension is a common endpoint for progressive liver disease, and can clinically manifest as refractory ascites, splenomegaly, and life-threatening esophageal and gastric variceal bleeding. Transjugular intrahepatic portosystemic shunt (TIPS) is an endovascular procedure that treats portal hypertension by making a connection between the portal and systemic venous systems. By creating a low-resistance outflow tract for portal venous drainage, TIPS decreases portal hypertension and its dangerous sequelae in patients not responding to medical therapy.